2018
DOI: 10.1242/jeb.182600
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of embryonic regulation of maternally derived yolk corticosterone

Abstract: In recent years, the potential for maternal stress effects to adaptively alter offspring phenotype has received considerable attention. This research has identified offspring traits that are labile in response to maternal stress; however, an understanding of the mechanisms underlying these effects is lagging and is crucial to appreciating the significance of this maternal effect. In the present study, we sought to better understand maternal stress effects by examining the potential for embryonic regulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 65 publications
1
17
0
Order By: Relevance
“…This could be because the stress sessions did not induce a similar magnitude of corticosterone deposition as occurred in CORT treatment or because both the hen and embryo possess the capacity to regulate maternally derived corticosterone. As previously reported ( Vassallo et al., 2014 , Vassallo et al., 2019 , Carter et al., 2018 ), embryos can modulate their developmental environment through rapid metabolization of free corticosterone in the egg. In addition, the catalytic activity of enzymes such as 11β-hydroxysteroid dehydrogenase located in the ovary follicles of hens can reduce the concentration of corticosterone in the yolk ( Rettenbacher et al., 2013b ).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…This could be because the stress sessions did not induce a similar magnitude of corticosterone deposition as occurred in CORT treatment or because both the hen and embryo possess the capacity to regulate maternally derived corticosterone. As previously reported ( Vassallo et al., 2014 , Vassallo et al., 2019 , Carter et al., 2018 ), embryos can modulate their developmental environment through rapid metabolization of free corticosterone in the egg. In addition, the catalytic activity of enzymes such as 11β-hydroxysteroid dehydrogenase located in the ovary follicles of hens can reduce the concentration of corticosterone in the yolk ( Rettenbacher et al., 2013b ).…”
Section: Discussionsupporting
confidence: 66%
“…The effects of maternal stress on egg composition have been extensively studied in birds (e.g., hormones ( Carter et al., 2018 ), antioxidants ( Possenti et al., 2018 ), and immunoglobulins ( Roth et al., 2018 )). Gonadal steroid hormones, and particularly androgens, are known to be important mediators of maternal effects.…”
Section: Introductionmentioning
confidence: 99%
“…Given the demonstrated phenotypic effects of corticosterone treatment in similar contexts, the lack of increase in tissue corticosterone could be explained by what we know of yolk hormone movement. The metabolism of corticosterone by the embryo is rapid (Carter et al, 2018), as is the conversion of the steroid from its lipid‐soluble to water‐soluble forms via reversible sulfonylation (Moore & Johnston, 2008; Paitz & Bowden, 2008). Our tissue corticosterone extractions and measurements targeted only lipophilic free corticosterone, and it is possible that this method obscured differences in levels of corticosterone metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…Also using a single egg injection of corticosterone prior to incubation, Janczak et al (74) observed that chicks from injected eggs stayed longer in TI but only if they had been previously handled, suggesting that life experiences influence this behavioral effect of maternal stress. Interestingly, physiological studies on maternal stress and the HPA axis activation of the offspring showed that treatment effects are only observed when the offspring is also subjected to stressors (75)(76)(77). Therefore, a combination of maternal stress and life experience might be essential to trigger behavioral and physiological responses in the offspring.…”
Section: Limitations and Effects Of The Stress Treatmentsmentioning
confidence: 99%